PENGURANGAN BEBAN KERJA TEKNISI LISTRIK DAN MEKANIK CV. GUNUNG MURIA MELALUI INTERVENSI ERGONOMI - Lamto Widodo; Adianto; I Wayan Sukania (Universitas Tarumanagara, 2026)
Gunung Muria is a company engaged in the sale, purchase, and generator service. From the results of the SSRT and NBM questionnaires, it was found that workers with the highest level of fatigue and musculoskeletal complaints were in the electrical technician work unit and mechanic. For the flip generator engine work posture get RWL and LI calculation with LI result of 12,83 so it has a musculoskeletal risk. The next stage is to design work tools using the Analytical Hierarchy Process (AHP) method. With the use of workbench tools, the value of the level of ergonomic risk decreased from before. REBA scores on generator engine servicing activities decreased from 7 to 3 in sitting and standing positions, flip the generator engine down from 10 to 5 in a sitting position and 2 in a standing position, genset engine side service decreased from 8 to 3 in the seated position and 2 in the standing position. OWAS scores for all activities decreased to 1. The results of the NBM questionnaire showed that physical complaints were reduced from 14 to 5 body parts.